TINJAUAN VARIABEL REFRIGERANT VOLUME - Rachman, Arfidian; Yuana Dewi, Arfita; Effendi, Asnal; Nesti, Lisa (ITP Press, 2023)
VRV systems are multi-split HVAC systems that maintain different portions by varying refrigerant volume. These systems control refrigerant volume for efficiency and dependability. This review aims to identify VRV system elements affecting operational and performance factors. Previous studies are crucial for future large-scale VRV development.